Kemampuan Beban Pajak Tangguhan, Akrual dan Size Untuk Mendeteksi Manajemen Laba Ability of Deferred Tax Expense, Accrual and Size for Detecting Earnings Management (Students' Journal of Accounting and Banking, 2012)
This study aimed examine the effect of the deferred tax asset and analyze, discretionary accruals and earnings management on the size of a manufacturing company that went public in Indonesia.The population in this study is a company engaged in the manufacturing sector are listed in Indonesia Stock Exchange (BEI) in 2008-2010. According to established criteria contained 37 samples. Analysis technique used is logistic regression.The results showed that the deferred tax liabilities have no effect on earnings management. Meanwhile, discretionary accruals and size effect on earnings management.Keywords: Earnings Management, Deferred Tax liabilities, Discretionary Acruaals, Size